Transferring Randasitagi and Wairiwondu Folktales into Video Storytelling Content as Literacy Learning Media for Junior High School Students in Buton Islands - Nurul Hafidzah Asra; Sumiyadi Sumiyadi; Halimah Halimah (KEMBARA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2025)
The low interest and critical literacy skills of students in the archipelago, especially the Buton Islands, are a serious challenge in literacy education. This problem is exacerbated by the limited learning media contextual and relevant to the local culture. This research aims to shift the form of Randasitagi and Wairiwondu folklore from traditional narrative texts to video storytelling content as an interactive and culture-based literacy learning medium. The method used is qualitative descriptive with a case study approach. Data was collected through interviews with teachers and students, learning observations, and documentation of junior high school students' learning outcomes. The study results show that converting folklore into videos can increase students' attraction to literacy materials, encourage active cognitive engagement, and stimulate critical and argumentative thinking skills in debate and discussion sessions. Video storytelling based on local stories has proven more effective than conventional text media in bridging students' cultural context with learning content. This study concludes that transforming local narratives into multimodal visual formats serves as cultural preservation and a pedagogical strategy relevant to the literacy needs of the 21st century. These findings open up opportunities for further development in folklore-based interactive media from various other regions to be applied in school contextual learning.